Top Performance in Investments in the Hungarian Economy - Báger, Gusztáv; Cseh, Tímea (Public Finance Quarterly, 2020)
The study shows that the extraordinary growth of fixed capital formation and investment was twice higher than the increase in GDP during the period between 2012 and 2018. Investment rate reached 25 percent in 2018, compared with the European Union’s 20.4 percent; after Sweden and the Czech Republic Hungary had the third highest rate among the EU Member States. The achievement of this outstanding investment performance was greatly supported by the use of EU funds, the growth in foreign direct investment inflow and the lending turnaround stimulated by the proactive and innovative monetary policy of the Hungarian Central Bank as well as the large-scale expansion of investment grants. Among these impact factors the use of EU funds was the most significant in years 2013-2015. These resources amounted to more than one third of government investments in the period under examination. The volume of foreign direct investment inflow reached 4 percent of GDP in four years during the period between 2012 and 2018. The impact of the Funding for Growth Scheme launched by the Hungarian Central Bank was 4.4 percentage points in years 2013-2018. In parallel with the boost in investment, there was a positive and efficient change in the industries and branches of the national economy, material-technical composition, territorial distribution, sectoral composition, as well as the structure of public investments according to institutional framework.